Pengaruh Kepemilikan Institusional, Komisaris Independen, Komite Audit, Solvabilitas, dan Likuiditas terhadap Nilai Perusahaan - Yonathan, Claudya; Apriwenni, Prima (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
The purpose of this research is to explore the influence of institutional ownership, independent commissioners, audit committee, solvency, and liquidity on firm value. This research uses agency theory and signaling theory as the basis for analysis. Financial statements of 55 consumer non-cyclicals listed on the Indonesia Stock Exchange (IDX) in 2021-2023 with a total of 165 samples became secondary data in the research. Retrieval sampling was carried out utilizing the purposive sampling method. Data processed utilizing multiple linear regression assisted by SPSS 25. The research output explains institutional ownership, independent commissioners, and liquidity have no influence on firm value. influence on firm value. The audit committee has negative influence on firm value, while solvency shows a positive influence on firm value. positive influence on firm value. The conclusion of the research confirms that solvency is a factor that contributes to the increase in firm value, but other variables do not have a significant impact. but other variables do not have a significant impact.